Model Servqual Rule Base Asean University Network untuk Penilaian Kualitas Program Studi - Wijayanti, Esti; Farikhin, Farikhin; Gernowo, Rachmat (Universitas Diponegoro, 2016)
As well known that AUN (Asean University Network.AUN) and ABET (Accreditation Boardb for Enginnering and Technology) are non-profit organitatinon which have. AUN (Asean University Network) were using variable with refer to AUN’s criteria’s there consist of fifteen which are: Expected Learning Outcomes, Programme Specification, Programme Structure and Content, Teaching and Learning Strategy, Student Assessment, Academic Staff Quality, Support Staff Quality, Student Quality, Student Advice and Support, Facilities and Infrastructure, Quality Assurance of Teaching/Learning Process, Staff Development Activities, Stakeholders Feedback, Output, Stakeholders Satisfaction,and adopted score's scale 7. In there here, we discuss the fifteen AUN’s of AUN in the criterias. There servqual of as can be into five dimensions, assurance, empathy, responsive, reliability and facilty in order to make the assessment's process easier. This research outcome indicated that this proposed method can be used to evaluate an education program. The validation result by using AUN's data and the analysis of servqual rule base Asean University Network almost have the same pattern with correlation value is 0,985 and this is can be accepted because its validity have reach 97%.